Tingkat Akurasi Shooting Jude Bellingham di Liga Champions Musim 2023-2024 - Dewa Akbar (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Football is a team sport, football played by two teams of 11 player each teams.the aim of football is to score as many goals into the opponents goal. Shooting or kicking the ball is one of the basic technique of playing football. The factors that can influence the succes rate of a shooting is accuracy. Champions league is a football competition held by UEFA and participate by the European clubs. Jude Bellingham is an english footballer who play as a midfielder for Real Madrid, Jude Bellingham known for his good accuracy, therefore the author is interested in making research about “Jude Bellingham’s shooting accuracy rate in the champions league season 2023-2024.”. The formulation of the problem in this research is (1) What is Jude Bellingham’s accuracy rate in the champions league season 2023-2024?, (2) Where is the most effective positions for Jude Bellingham to score goals?, (3) what technique Jude Belingham used to score a goal?.the research methode used in this research is descriptive quantitative, the purpose of this research is to know the shooting accuracy rate of Jude Bellingham in the Champions league season 2023-2024, to know what technique Jude Belingham used to score a goal, and to know where is the most effective positions for Jude Bellingham to score goals, by collecting statistic data of Jude Bellingham and then analyze Jude Bellingham’s shooting accuracy rate to know the shooting percentage, most effective positions for Jude Bellingham to score, and what technique used by Jude Bellingham to score goals.